Justice as fairness, progress and perfection - Otero Angelini, Diego Alejandro (Revista de Humanidades de Valparaíso, 2020)
In this article I analyze the justification of rawlsian anti-perfectionism, present in both A Theory of Justice and Political Liberalism. My aim is to show how justice as fairness, Rawls’s conception of justice, lacks stability because of it. As an alternative to his anti-perfectionism, I propose, in the second part, the idea of progress as practical perfectionism by John Dewey. I argue that a perfectionist liberalism of this kind does not undermine reasonable pluralism as Rawls argued. Also I argue that it is indispensable to establish a liberal society that is stable. In the end, I briefly show how the private sphere could be affected once the idea of progress is part of a conception of liberal justice.